THE CENTRAL ROLE OF WORK–LIFE BALANCE AND CAREER DEVELOPMENT ON WORK MOTIVATION: AN EMPIRICAL STUDY IN INDONESIAN LOCAL GOVERNMENT AGENCY - Rachmat Hamid; Bambang Supriadi; Harianto Respati; Feriska Andriani (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study investigates the direct and indirect influence of Work–Life Balance (WLB) and Career Development (CD) on Work Motivation (WM) among employees in the Indonesian public sector, specifically at the Regional Revenue Agency (BAPENDA) of Malang Regency. The research aims to clarify the mixed empirical findings regarding the determinants of public-sector motivation and to provide practical implications for Human Resource Management (HRM) policies. A quantitative explanatory research design was employed, using a survey-based approach with a saturated sample of 192 BAPENDA Malang Regency employees (54% female, 74% with undergraduate degrees). Data were collected using a structured questionnaire, and the hypotheses were tested using Structural Equation Modeling with Partial Least Squares (PLS-SEM). Descriptive analysis revealed a highly positive organizational climate, with all three variables (WLB, CD, and WM) rated as "High" to "Very High." Career Development recorded the highest mean score (4.4611). The structural modeling results showed that WLB is the most powerful determinant of Work Motivation, explaining the psychological stability and emotional energy needed for sustained enthusiasm. Career Development also significantly influences WM but plays a more modest, supplementary role. Crucially, the analysis confirmed a partial mediation effect, indicating that the positive impact of Career Development on motivation is partially channeled through employees’ perceptions of Work–Life Balance. This study provides robust empirical evidence from a scarce context—Indonesian regional government institutions—where motivational patterns often differ due to bureaucratic rigidity and formalized structures. It underscores that for strategic HRM improvements in the public sector, the most effective approach is a dual emphasis on protecting daily well-being (WLB) and cultivating meaningful opportunities for growth (CD). The findings highlight that WLB should be prioritized as a prerequisite for maximizing the motivational benefits of career development initiatives